2016
DOI: 10.1016/j.spasta.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

A spatio-temporal comparison of avian migration phenology using Citizen Science data

Abstract: Please cite this article as: Arab, A., Courter, J.R., Zelt, J., A spatio-temporal comparison of avian migration phenology using Citizen Science data. Spatial Statistics (2016), http://dx. AbstractThe effects of climate change have wide-ranging impacts on wildlife species and recent studies indicate that birds' spring arrival dates are advancing in response to changes in global climates.In this paper, we propose a spatio-temporal approach for comparing avian first arrival data for multiple species. As an exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…For this reason, big data are greatly advancing our understanding of avian phenology, including the timing of migration and breeding phenophases. Some big data resources, such as the citizen science project Journey North, focus exclusively on aspects of phenology such as migration arrival (Arab et al 2016). Likewise, eBird is increasingly being used to understand migration phenology, particularly how the timing of migration has been shifting in response to recent climate change, and the extent to which these shifts vary geographically and with species traits (Hurlbert and Liang 2012, Mayor et al 2017).…”
Section: Past and Present Contributions To Ornithologymentioning
confidence: 99%
“…For this reason, big data are greatly advancing our understanding of avian phenology, including the timing of migration and breeding phenophases. Some big data resources, such as the citizen science project Journey North, focus exclusively on aspects of phenology such as migration arrival (Arab et al 2016). Likewise, eBird is increasingly being used to understand migration phenology, particularly how the timing of migration has been shifting in response to recent climate change, and the extent to which these shifts vary geographically and with species traits (Hurlbert and Liang 2012, Mayor et al 2017).…”
Section: Past and Present Contributions To Ornithologymentioning
confidence: 99%
“…Several models that account for spatial dependency have also been developed within the Bayesian framework for citizen science data (Humphreys et al., 2019). Conditional autoregressive (CAR) priors have been found to adequately capture spatial variability in some studies (Arab & Courter, 2015; Arab et al., 2016; Pagel et al., 2014; Purse et al., 2015), while Gaussian random fields (Humphreys et al., 2019) and stochastic partial differential equations (SPDE) (Peterson et al., 2020) have been successfully used in others. To our knowledge, no one has addressed the issue of misclassification in citizen science accounting for spatial dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Several biases from the data sources have been considered in the results. It has been shown that increased observers result in seemingly earlier arrival dates Arab et al, 2016). However, an argument for the integrity of the sources in this study can be made.…”
Section: Discussionmentioning
confidence: 64%
“…For both analyses, avian first arrival dates and wildflower blooming dates, the data sources were evaluated for credibility and accuracy before combining the datasets. Specifically for first arrival dates, more observers may result in seemingly earlier arrival dates Arab et al 2016). We reconciled our avian sources with these issues by arguing that all observers were experienced naturalists who visited a variety of habitats to observe migrating species and that the data from each source were gathered by groups of people more often than by single individuals, which improved consistency among sources.…”
Section: Uncovering and Processing Historical Sourcesmentioning
confidence: 99%
See 1 more Smart Citation